Embroidered electrodes for bioelectrical impedance analysis: impact of surface area and stitch parameters. (3rd September 2019) - Logothetis, Irini; Fernandez-Garcia, Raul; Troynikov, Olga; Dabnichki, Peter; Pirogova, Elena; Gil, Ignacio
Abstract: Measuring electrical activity in the human body is vital in the diagnosis and monitoring of patients; thus, attention to the design of biopotential electrodes is essential. It is important that electrodes are designed accordingly by adapting to a specific device and application. By embroidering electrodes, we can tailor the electrode parameters to suit the application and integrate them into textile outfits. However, embroidered electrodes possess unwanted polarizing impedance ( ) relative to the frequency of the current applied by the system. Dry embroidered electrodes are preferred to wet electrodes for bioelectrical impedance analysis (BIA) recordings providing stable measurements. BIA is a relatively simple and non-invasive technique that measures the resistivity of biological tissue. This research analyzes the impact of embroidery characteristics (i.e. electrode surface area, stitch type, stitch density and stitch length) on embroidered electrodes by identifying the parameters reducing for BIA in a dry and wet state. In addition, the influence of the amount of conductive thread utilised for the fabrication of the sample electrodes was studied. For dry electrodes, we identified that a larger electrode surface area, increased stitch length and stitch density reduce . Moreover, it was observed that potentially there is a threshold on the amount of conductive yarn used for the embroidered electrode. In contrary, wet electrodes displayed irregular and thus, it can be concluded that they could potentially impair BIA measurements. In essence, our findings show that embroidered electrodes can be incorporated into wearable BIA systems for health monitoring in home settings.